HOW CSR PROGRAMS INFLUENCE CORPORATE IMAGE: INSIGHTS FROM CUSTOMERS OF BRI MANNA BRANCH - Meilaty Finthariasari; Anisa Rahma Putri (Universitas Muhammadiyah Bengkulu, 2026)
This study examines the effect of customer perceptions of Corporate Social Responsibility (CSR) programs on the corporate image of Bank Rakyat Indonesia (BRI) Manna Branch, South Bengkulu Regency. Using a descriptive research design, the study targeted BRI customers who had received or were aware of the CSR programs implemented by the branch. Data were collected through observation, interviews, and questionnaires. Descriptive analysis, simple linear regression, and the coefficient of determination (R²) were employed using SPSS. The findings reveal that customer perceptions of CSR programs have a positive and significant effect on the corporate image of BRI Manna Branch. This indicates that more favorable perceptions of CSR initiatives are associated with a stronger corporate image among customers. The results highlight the importance of implementing well-targeted and sustainable CSR programs, supported by effective communication, to enhance customer perceptions and strengthen the bank’s reputation. Consequently, BRI Manna Branch should continue to develop and improve its CSR initiatives to ensure that their benefits are widely experienced by communities in need while simultaneously reinforcing the bank’s positive image